2004
DOI: 10.2134/jeq2004.2030
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Root Density along Stream Banks

Abstract: While it is recognized that vegetation plays a significant role in stream bank stabilization, the effects are not fully quantified. The study goal was to determine the type and density of vegetation that provides the greatest protection against stream bank erosion by determining the density of roots in stream banks. To quantify the density of roots along alluvial stream banks, 25 field sites in the Appalachian Mountains were sampled. The riparian buffers varied from short turfgrass to mature riparian forests, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 28 publications
0
29
1
1
Order By: Relevance
“…The streambank soils of all land uses in the current study generally have a low P release potential and, in some situations, may actually serve as sinks for dissolved forms of P. The interior of cornfields and hayfields, if eroded by extreme weather events, such as happened with Tropical Storm Irene in the northeastern United States in 2011 (Vidon et al, 2018), would most likely contribute to Lake Champlain as sources of P, as they are high in TP and have higher DPS. Clearly, land use strategies that include practices such as exclusionary fencing for cattle and vegetated buffer zones are important to lower the rate of streambank erosion (Laubel et al, 2003;Wynn et al, 2004). However, these riparian strategies will need to be combined with strategies to mitigate upgradient agricultural sources, such as by drawing down soil P (phytomining, tillage, and even P sorbing amendments) and minimizing erosion.…”
Section: Factors Affecting Phosphorus Exportmentioning
confidence: 99%
“…The streambank soils of all land uses in the current study generally have a low P release potential and, in some situations, may actually serve as sinks for dissolved forms of P. The interior of cornfields and hayfields, if eroded by extreme weather events, such as happened with Tropical Storm Irene in the northeastern United States in 2011 (Vidon et al, 2018), would most likely contribute to Lake Champlain as sources of P, as they are high in TP and have higher DPS. Clearly, land use strategies that include practices such as exclusionary fencing for cattle and vegetated buffer zones are important to lower the rate of streambank erosion (Laubel et al, 2003;Wynn et al, 2004). However, these riparian strategies will need to be combined with strategies to mitigate upgradient agricultural sources, such as by drawing down soil P (phytomining, tillage, and even P sorbing amendments) and minimizing erosion.…”
Section: Factors Affecting Phosphorus Exportmentioning
confidence: 99%
“…However, in low-gradient Coastal Plain streams much of the CPOM becomes buried within the sandy stream beds following floods (Metzler and Smock 1990;Smock 1990). Roots of riparian trees are important in stabilizing stream banks (e.g., Gregory and Gurnell 1988;Thorne 1990;Wynn et al 2004), and they can also be common (24% of CPOM) within intermittent Coastal Plain stream beds (Fritz et al 2006a). However, the role of roots as food or habitat for invertebrates within intermittent channels is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Surface soil horizons generally have a higher density of roots as these horizons have higher nutrient and oxygen concentrations and lower soil bulk density (McGinty 1976;Gray and Leiser 1982;Coppin and Richards 1990). Wynn et al (2004) found that RLD decreased with increasing soil depth and root diameter. Findings in the current study agree with results from other studies.…”
Section: Resultsmentioning
confidence: 94%